Assessment of obesity indices and disease severity in male patients with obstructive sleep apnea: a cross-sectional study - Ahmed Gharib; Mai S. Elsheikh; Yasmine H. El-Hinnawy; Gehan Hamdy (Journal of the Arab Society for Medical Research)
Background/aim Obstructive sleep apnea (OSA) is associated with multiple chronic conditions and increased risks of complications and mortality. The relationship between OSA and obesity is complex but increased body fat is widely recognized as a major risk factor for OSA. This work aims to determine the cut-off values of the body mass index (BMI), waist to hip ratio (WHR), neck circumference (NC) that can be used to predict the occurrence of OSA and its severity. Patients and methods This observational cross-sectional study included 241 Egyptian male patients, complaining from symptoms of OSA. The patients were subjected to measurements of obesity indices and underwent polysomnography to confirm the diagnosis of OSA according to the recommended guidelines for the manual scoring of respiratory events. Results The present study exhibited a significant association between BMI, WHR and NC with different polysomnographic parameters. BMI, NC, and WHR were the most significant predictors of OSA (P<0.05). Cutoff values reported 34.35 kg/m2 for BMI with 73.2% sensitivity and 69.4% specificity, while for NC reported 42.5 cm with 68.3% sensitivity and 75.5% specificity, and for WHR exhibited 1.0259 cm, with 59.9% sensitivity and 65.3% specificity. The severity of OSA in male sex was associated with older age, increased BMI, NC, WHR. The severity of OSA was also associated with decreased O2 saturation and higher Desaturation index, Arousal index, and snoring index. Conclusion Increased BMI, NC, and WHR were the most significant predictors of OSA and correlated with the severity of the disease in male patients.